Democratic consolidation in Eastern Europe. - Zielonka, Jan, 1955- (Oxford University Press, 2001)
This collection of papers is part of a series on democratic consolidation in post-communist Central and Eastern Europe. This first volume analyses constraints on and the opportunities provided by institutional engineering.
Keywords: Democratization -- Europe, Eastern.; Democratization -- Former Soviet republics.; Constitutional history -- Europe, Eastern.; Constitutional history -- Former Soviet republics.; Europe, Eastern -- Politics and government -- 1989-; Former Soviet republics -- Politics and government.; Démocratisation -- Europe de l'Est.; Démocratisation -- Ex-URSS.; Histoire constitutionnelle -- Europe de l'Est.; Histoire constitutionnelle -- Ex-URSS.; Europe de l'Est -- Politique et gouvernement -- 1989-; POLITICAL SCIENCE -- Political Process -- General.; Constitutional history; Democratization; Politics and government; Eastern Europe; Soviet Union -- Former Soviet republics; Since 1989